Optimization of video quality via fuzzy logic base adaptive media playout - Farij Ehtiba; Badlishah Ahmad; Mostafijur Rahman (Institute of Advanced Engineering and Science, 2019)
This paper addresses the issue of interruption of Virable Bit Rate (VBR) video streaming over IP network, due to channel quality fluctuation. Specifically, a Fuzzy Logic (FL) Control principle is fused with Adaptive Media Playout (AMP) control to estimate an appropriate playout frame rate, namely FLAMP. Based on the estimation of the playout frame rate, the FLAMP algorithm adjusts the consumption rate smoothly to avoid video stream degradation. Simulation results validate that the FLAMP scheme efficiently reduces the buffer outage probability and provides better visual quality where FLAMP gives 26.5% less ferquence of playout interruption, and 21.6% less variance of distortion of playout as compared to APTA.